Դիտարկումներ Ջուղայի բարբառի վերաբերյալ տարաժամանակյա հայեցակետով - Վարդանյան, Արտակ (ՀՀ ԳԱԱ ԼԻ հրատ.)
The dialect of Old Jugha has been preserved almost without flaws in New Jugha, however, an interesting change has occurred in the consonant system of the village of Jugha, located near Old Jugha – the four-row consonant system of the subdialect has turned into a three-row one – aspirated voiced at the beginning of a word have turned into voiceless (բ՛ գ՛ դ՛ ձ՛, ջ՛ > պ, կ, տ, ծ, ճ), and in the middle of a word and at the end of words – into simple voiced or voiceless (բ՛ գ՛ դ՛ ձ՛, ջ՛ > բ, գ, դ, ձ, ջ or պ, կ, տ, ծ, ճ), the diphthongs ե and ո have been partially preserved, palatal vowels, which are not characteristic of the Jugha dialect, are evident not only in borrowed words, but also in native Armenian words. Opposite the most commonly used particle ներ, which forms the plural, there is a particle նի: Verbs of conjugation ել in the infinitive form have the ending իլ. Formations with the ending ման of monosyllabic verbs of the indicative mood disappeared in the middle of the last century, they were replaced by forms with ըմ. Along with obvious lexical communities, there are also certain differences. The above-mentioned deviations in dialectal features are undoubtedly the result of interdialectal relations that take place between Jugha and Ararat, Khoy and other nearby dialects. Джугинский диалект почти без изъяна сохранился в Новой Джуге, однако в системе согласных говора села Джуги, находящегося вблизи Старой Джуги, произошло ряд интересных изменений. Четырехрядная система согласных диалекта превратилась в трехрядную – придыхательные звонкие в начале слова превратились в глухие (բ՛ գ՛ դ՛ ձ՛, ջ՛ > պ, կ, տ, ծ, ճ), а в середине слова и в конце слов – в простые звонкие или глухие (բ՛ գ՛ դ՛ ձ՛, ջ՛ > բ, գ, դ, ձ, ջ или պ, կ, տ, ծ, ճ), дифтонги ե и ո сохранились частично, налицо не характерные для Джугинского диалекта палатальные гласные не только в заимствованных словах, но и исконно армянских словах. Напротив самой употребительной частицы ներ, образующей множественное число, налицо частица նի: Глаголы сопряжения ել в неопределенной форме имеют окончание իլ. Образования с окончанием ման односложных глаголов изъявительного наклонения исчезли в середине прошлого века, их заменили формы с ըմ. Рядом с очевидными лексическими общностями налицо также определенные различия. Вышеуказанные отклонения диалектных признаков, несомненно, являются результатом междиалектных отношений, имеющих место между Джугинским и Араратским, Хойским, а также другими близлежащими диалектами.
Keywords: Բարբառագիտություն